(untitled) - Stuart, Jonathan (London, 1996)
A wide-ranging, illustrated guide to creating and maintaining a healthly aquarium covers everything the beginning hobbyist needs to know about freshwater and marine home aquariums, from establishing a flourishing ecosystem to overcoming problems.
Keywords: Tropical fish,Aquarium fishes